Development of new powdery mildew resistant lines in garden pea (Pisum sativum L.) using induced mutagenesis and validation of resistance for the er1 and er2 gene through molecular markers - Sharma, Akhilesh; Banyal, Devinder Kumar; Dhole, Vinod Janardan; Bansuli,; Rana, Ranbir Singh; Kumar, Rajesh; Kumar, Prabhat; Kumar, Nimit; Srishti,; Prashar, Arshia; Singh, Vivek; Sharma, Anoushka (Frontiers in Plant Science, 2025)
Powdery mildew (PM) caused by Erysiphie pisi Syd. is the most devastating disease of pea, affecting fresh pea production as well as the quality of the marketable harvest worldwide. The efforts were made to develop PM-resistant mutants of popular pea varieties “Lincoln” and “Azad P-1” through induced mutations by following gamma irradiation (300, 400, 500, and 600 Gy) and chemical mutagenesis, i.e., ethyl methane sulfonate (EMS) (0.3% and 0.4%). The screening of 13,868 M2 progenies at Kukumseri (summer season) followed by M3 generation at Palampur (winter season) resulted in the isolation of six putative PM-resistant mutants. The rigorous evaluation of these progenies under in vivo (field screening) and in vitro (artificial screening under greenhouse conditions and using the detached leaf assay method) conditions over the years resulted in the isolation of three PM-resistant mutants, viz., L-40-1014, L-0.3-139, and AP-0.3-129. SSR markers “PSMPSAD60 d” and “PSMPA5 c” linked to the er-1 gene indicated the presence of the “er1” gene in the mutant L-0.3-139 while the er-2 gene-linked SCAR marker “ScX171400” and SSR marker “AD141” indicated the probability of the “er-2” gene in mutant L-40-1014. The known markers linked to PM resistance genes could not be validated in the mutant AP-0.3-129, suggested to identify new markers linked to PM resistance. These PM-resistant mutants can be promising candidates as the new source of resistance for future pea breeding programs.